Measurements of galactic cosmic ray shielding with the CRaTER instrument. Issue 5 (22nd May 2013) - Zeitlin, C.; Case, A. W.; Spence, H. E.; Schwadron, N. A.; Golightly, M.; Wilson, J. K.; Kasper, J. C.; Blake, J. B.; Looper, M. D.; Mazur, J. E.; Townsend, L. W.; Iwata, Y.
Abstract : The Cosmic Ray Telescope for the Effects of Radiation (CRaTER) instrument aboard the Lunar Reconnaissance Orbiter has been measuring energetic charged particles from the galactic cosmic rays (GCRs) and solar particle events in lunar orbit since 2009. CRaTER includes three pairs of silicon detectors, separated by pieces of tissue‐equivalent plastic that shield two of the three pairs from particles incident at the zenith‐facing end of the telescope. Heavy‐ion beams studied in previous ground‐based work have been shown to be reasonable proxies for the GCRs when their energies are sufficiently high. That work, which included GCR simulations, led to predictions for the amount of dose reduction that would be observed by CRaTER. Those predictions are compared to flight data obtained by CRaTER in 2010–2011. Key Points: CRaTER measures the shielding effects of cosmic rays by TEP Measurements are compared both to model predictions and accelerator data The results agree with predictions from models and accelerator data